The Association of Body Mass Index, Physical Activity and Hypertension in Indonesia - Hodimatum Mahiroh; Erni Astutik; Rochmad Ardiansyah Pratama (Jurnal Ners, 2019)
Introduction: Hypertension can cause cardiovascular disease, and it is still aserious global problem. The Prevalence of hypertension has increased every year.Some of the factors associated with hypertension are obesity and physical activity.The prevalence of obesity has increased every year, and many people have lowerlevels of physical activity. This study aims to analyse the correlation between BodyMass Index (BMI), physical activity and hypertension in Indonesia.Methods: This study used a cross-sectional study design using secondary datafrom the Indonesia Family Life Survey 5 (IFLS5) conducted in 2014 - 2015. Thesample consisted of individuals in the households interviewed and 26,472Respondents fulfilled the criteria. The data were analysed using multivariate logisticregression.Results: The results showed that most of the respondents were of productive age.More than half of the respondents were female (52.05%). The respondents whoHad hypertension totalled 22.63 %. After being controlled by the covariatevariables, the results showed that the obese respondents had 4.08 times higherodds of experiencing hypertension compared to the normal respondents (AOR=4.08, 95% CI = 3.68-4.53, p-value = 0.000) and that the respondents who wereoverweight were 2.49 times likely to get hypertension compared to therespondents who were normal (AOR = 2.49, 95% CI = 2.32-2.67, p-value = 0.000).Meanwhile, the respondents with an underweight BMI were 0.58 times more likelyto have hypertension compared to the respondents who were normal (AOR = 0.58,95% CI = 0.52-0.65, p-value = 0.000).Conclusion: Individuals with a higher BMI will be more at risk of hypertensionWhile physical activity is not related to hypertension. The government and healthservices need to increase the promotion of a healthy lifestyle, exceptionally robustdiet programs, to encourage the population to maintain ideal body weight andto reduce the rate of hypertension.